2021
DOI: 10.1002/cjoc.202100140
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Sugar Alcohols over a Synergistic and Sustainable Catalyst

Abstract: Main observation and conclusion A series of catalysts were prepared for sugar alcohols production to overcome the deficiencies of the previous reported catalysts, such as low yield of sugar alcohols, single function, instability, and controversial role of active sites. The role of each metal and their synergistic‐cooperation was discussed in detail with a combination of conditional experiments and characterizations. The results indicated that bifunctional Ni6.66Fe1Al1.55 catalyst has unique structure with supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…For instance, Mishra et al 123 studied the liquid phase selective hydrogenation of D-glucose over the solid Ru(1.0%)/ NiO(5.0%)-TiO 2 catalyst, in which about 96% glucose conversion and 98.5% selectivity of d-sorbitol was realized at 120 °C under a 5.5 MPa of H 2 ; then, Hernandez-Mejia et al 124 found that up to 98% yield for xylitol could be obtained from the xylose hydrogenation over Ru/TiO 2 (rutile) at 120 °C after 15 min. Moreover, Zhang et al 125 further investigated the catalytic activity of the Ni 6.66 Fe 1 Al 1.55 catalyst for the hydrogenation of xylose, where ca. 99.8% yield of xylitol could be acquired with a Ni-Al−O x spinel structure at 120 °C under a 3 MPa pressure of H 2 ; similarly, the yield of sorbitol reached 98.9% with the Ni 6.66 Fe 1 Al 1.55 catalyst.…”
Section: Biomass Valorizationmentioning
confidence: 99%
“…For instance, Mishra et al 123 studied the liquid phase selective hydrogenation of D-glucose over the solid Ru(1.0%)/ NiO(5.0%)-TiO 2 catalyst, in which about 96% glucose conversion and 98.5% selectivity of d-sorbitol was realized at 120 °C under a 5.5 MPa of H 2 ; then, Hernandez-Mejia et al 124 found that up to 98% yield for xylitol could be obtained from the xylose hydrogenation over Ru/TiO 2 (rutile) at 120 °C after 15 min. Moreover, Zhang et al 125 further investigated the catalytic activity of the Ni 6.66 Fe 1 Al 1.55 catalyst for the hydrogenation of xylose, where ca. 99.8% yield of xylitol could be acquired with a Ni-Al−O x spinel structure at 120 °C under a 3 MPa pressure of H 2 ; similarly, the yield of sorbitol reached 98.9% with the Ni 6.66 Fe 1 Al 1.55 catalyst.…”
Section: Biomass Valorizationmentioning
confidence: 99%
“…Therefore, significant efforts have been dedicated to designing and developing catalysts for the green and efficient hydrogenation of glucose to sorbitol, including precious metals (e.g., Ru 12−15 and Pt 16,17 ) and nonprecious metals (e.g., Ni 11,18,19 and Cu 20 ). Although precious metals exhibit excellent catalytic activity for this reaction, their high cost and limited availability hinder their widespread industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…The Ni 6.66 Fe 1 Al 1.55 catalyst also provided a high sorbitol yield of 99% under relatively harsh reaction conditions (130 °C, 3 MPa H 2 , and 5 h). 19 In a word, the majority of the previously reported Ni-based catalysts still operated under a high H 2 pressure (3−5 MPa) and the sorbitol production efficiency also needs to be improved because of the relatively long reaction time in many cases (Table S1). In this light, the development of high-efficiency Ni-based catalysts that do not depend on high H 2 pressure and avoid a complex catalyst preparation process is highly desirable to replace the Raney Ni for the hydrogenation of glucose to sorbitol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations